2022
DOI: 10.1037/adb0000666
|View full text |Cite
|
Sign up to set email alerts
|

Pooled and person-specific machine learning models for predicting future alcohol consumption, craving, and wanting to drink: A demonstration of parallel utility.

Abstract: Background and Aims: The specific factors driving alcohol consumption, craving, and wanting to drink, are likely different for different people. The present study sought to apply statistical classification methods to idiographic time series data in order to identify person-specific predictors of future drinking-relevant behavior, affect, and cognitions in a college student sample. Design: Participants were sent 8 mobile phone surveys per day for 15 days. Each survey assessed the number of drinks consumed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 27 publications
4
41
0
Order By: Relevance
“…Thus, the sample average provided better prediction accuracy for these individuals than a personalized model. This finding is consistent with the parent study for the current data [2]. In addition, the models of craving and wanting to drink for P001, P010, craving for P006, P008, P023, wanting to drink for P018, and the models for drank/did not drink for P002 and P005 lack emotion variables altogether, and instead retained only time variables as predictors.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Thus, the sample average provided better prediction accuracy for these individuals than a personalized model. This finding is consistent with the parent study for the current data [2]. In addition, the models of craving and wanting to drink for P001, P010, craving for P006, P008, P023, wanting to drink for P018, and the models for drank/did not drink for P002 and P005 lack emotion variables altogether, and instead retained only time variables as predictors.…”
Section: Discussionsupporting
confidence: 89%
“…This study demonstrated the possibility that certain and separate emotions could predict craving alcohol, and unlike drank/did not drink or wanting to drink outcomes, craving on average was predominated by negatively valenced emotions. As shown in other analyses of these data, the present analysis showed that certain days of the week, Thursday through Sunday, were common predictors of craving, and were even more common predictors in the pooled model for whether a person drank [2]. While the pooled predictors may provide some insight into which theories of alcohol use best apply to college students in general, our results indicate that the relationship between emotions and alcohol use vary per person.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations